A qualitative synthesis of theories on psychosocial response to loss of breasts, limbs or teeth. (2020) - Al-Sahan, Maha M.; MacEntee, Michael I.; Thorne, Sally; Bryant, S. Ross
Abstract: Objectives: The aim of this systematic review is to generate a qualitative synthesis of psychosocial theories being used to explain the beliefs and behaviors of people responding to loss of anatomical parts, such as breasts, limbs, or teeth. Data & sources: A search in four databases and subsequent manual search of pertinent reference lists identified theories on how people respond to loss of anatomical parts. Findings were analyzed by consensus through a three-stage interpretive process to: deconstruct and interpret each theory, categorize similar theoretical constructs, and distill the dominant theoretical perspectives identified as most relevant to explaining responses to the loss. Study selection: 2540 citations produced 288 articles referring to 89 primary theories containing 586 constructs. Through synthesis of seven construct categories a metatheory with essential contributions from theories on communications, developmental regulation, emotions, resources, and social cognition can explain responses to loss. Conclusions: This qualitative synthesis provides a conceptual foundation for further investigations to explain how people manage loss of anatomical parts. Clinical significance: The combination of five dominant theories serves as a prelude to the development of a metatheory, which will further help determine how people psychosocially respond to the loss of anatomical parts.